Kawin Usia Muda: Apakah Masih Menjadi Tren di Kalangan Masyarakat Indonesia? - Suryawan. S, Dwi Ari; Jannah, Yasinta Amalia Nur (Seminar Nasional Official Statistics, 2024)
Marriage is an important phase in human life, especially first marriage. Discussion of first marriage cannot be separated from the age of first marriage. This is because the age of first marriage is often associated with reproductive health and socioeconomic problems. In Indonesia, there is a tendency where the age of first marriage of women is increasing. On the other hand, early marriage is still found in rural areas. In fact, early marriage has a negative impact on mothers and children’s health. Therefore, this study is conducted to examine whether there was a difference in the age of first marriage in Indonesian by gender, region (village or city), and province also the difference in the average age of first marriage in 2009 and 2022. Research data is BPS data in 2009 and 2022 which was analyzed using non parametric differential tests, namely Mann-Whitney and Kruskall Wallis tests. Result shows that there is a difference in the average age of first marriage in 2009 compared to 2022. In addition, there is also a difference in the average age of first marriage by gender, domicile, and province.